Patient-Specific Cardiac Magnetic Resonance Feature Tracking Approach for Scar Detection in Concomitant Ischemic and Non-Ischemic Heart Disease - Polacin, Malgorzata; Hünermund, Tobias; Müggler, Oliver; Alkadhi, Hatem; Kozerke, Sebastian; Manka, Robert (Cardiology and Cardiovascular Medicine, 2022)
Aim: This study investigated a patient-specific approach of using cardiac magnetic resonance (CMR) feature tracking for scar detection in a heterogenous patient group with chronic ischemic and non-ischemic heart disease. Methods: CMR exams of 89 patients with concomitant chronic ischemic and non-ischemic heart disease (IHD+) as well as 65 patients with ischemic scars only (IHD) were retrospectively evaluated. In all patients, global (GCS) and segmental circumferential strain (SCS) was derived from native cine images using a dedicated software (Segment CMR, Medviso). After calculation of patient-specific median GCS (GCSmedian), segmental values from GCSmedian percentage plots were correlated with corresponding myocardial segments in late gadolinium enhancement (LGE). Results: Overall GCS ranged between -3.5% to -19.8% and average GCS was lower in IHD+ than in IHD (p <0.05). In IHD, 19% of all myocardial segments were infarcted, in IHD+ 16.6%. Additionally, non-ischemic LGE was present in 6.7% of segments in IHD+. Correlation of GCSmedian percentage plots with corresponding LGE showed that presence of ischemic scar tissue in a myocardial segment was very likely below a cutoff of 39.5% GCSmedian (87.5% sensitivity, 86.3% specificity, AUC 0.907, 95% CI 0.875-0.938, p < 0.05). Conclusion: In patient-specific GCSmedian percentage plots calculated from native cine images, ischemic scar tissue can be suspected in myocardial segments below the threshold of 40% GCSmedian (sensitivity 88%, specificity 86%), even in a heterogenous patient cohort with ischemic and non-ischemic heart disease.